PERSEPSI PETANI PADI TERHADAP PROGRAM BILLING SISTEM DI KECAMATAN METRO BARAT KOTA METRO - Muher Sukmayanto; Erika Dwi Alviana; Abdul Muhtholib (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
This study aims to determine the perceptions of rice farmers on billing system programs. This research was conducted in Metro Barat District, Metro City. Sampling in this study used a purposive sampling technique, namely farmers from participants in the billing system program. The type of data used in this study are primary and secondary data. The method used in this study is a qualitative descriptive analysis method used to determine rice farmers' perceptions of billing system programs. The results of the study obtained farmers' perceptions of the billing system program seen from the program objectives in the good category. Farmers' perceptions of billing system programs seen from program implementation are still in the poor category. Farmers' perceptions of billing system programs seen from the benefits obtained by farmers are categorized as good.